Una sfinge mostruosa dalle braccia d’animale Alcune riflessioni sulla depersonalizzazione - Migliorini, Vanina; Fortes Lindau, Juliana; Telesforo, Ludovica; Fiori Nastro, Paolo (Il sogno della farfalla, 2010)
Depersonalization is still today a complex, undefined and obscure topic. At an international level, in the last few years, there has been a renewed and growing interest in this symptom, given that it is present to a high degree in a series of psychiatric pathologies. Psychiatric research has recently started concentrating, in particular, on the study of prodromic phases of schizophrenia, where, according to some, depersonalization features as a main symptom. In this article, the authors propose some reflections on depersonalization, prevalently from a clinical and psychopathological point of view, offering, moreover, some hypotheses on the cause of the symptom. The concept of depersonalization itself has undergone different passages throughout history, depending on the various philosophical and psychological schools, and these are briefly analyzed and discussed. Given the fact that it is a transnographic symptom that opens up a number of complex psychopathological pictures, the authors ask themselves if depersonalization can be considered a prodromic symptom indicating a clinical picture of neurosis or psychosis. After a brief overview of the literature the authors offer the hypothesis, backed up by a number of clinical cases, that depersonalization actually represents a modern version of hysteria: in a pathological process which can be located at puberty, from a pathological point of view, the causes of a psychic symptom are hypothesized to be closer to a hysteria than a schizophrenia, given its particular link with the body.